2017
DOI: 10.1101/gad.296962.117
|View full text |Cite
|
Sign up to set email alerts
|

Focus on cutaneous and uveal melanoma specificities

Abstract: Cutaneous melanoma (CM) and uveal melanoma (UM) derive from cutaneous and uveal melanocytes that share the same embryonic origin and display the same cellular function. However, the etiopathogenesis and biological behaviors of these melanomas are very different. CM and UM display distinct landscapes of genetic alterations and show different metastatic routes and tropisms. Hence, therapeutic improvements achieved in the last few years for the treatment of CM have failed to ameliorate the clinical outcomes of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 228 publications
0
91
0
Order By: Relevance
“…Nevertheless, gene expression profiling of uveal melanoma suggests two distinct phenotypes differentiated by either low or high risk that were characterized by differential expression of E-cadherin and the transcription factor Id1 (Onken et al 2004), and phenotypic plasticity has been observed in uveal melanoma cultures (Doherty et al 2017). Thus, while uveal melanoma has a different genetic basis than cutaneous melanoma, being driven by activating mutations in GNAQ or GNA11 (Van Raamsdonk et al 2009, 2010Pandiani et al 2017); nevertheless, it seems likely that phenotypic heterogeneity will play a key role in disease progression of noncutaneous melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, gene expression profiling of uveal melanoma suggests two distinct phenotypes differentiated by either low or high risk that were characterized by differential expression of E-cadherin and the transcription factor Id1 (Onken et al 2004), and phenotypic plasticity has been observed in uveal melanoma cultures (Doherty et al 2017). Thus, while uveal melanoma has a different genetic basis than cutaneous melanoma, being driven by activating mutations in GNAQ or GNA11 (Van Raamsdonk et al 2009, 2010Pandiani et al 2017); nevertheless, it seems likely that phenotypic heterogeneity will play a key role in disease progression of noncutaneous melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…The functioning of the epidermal unity is independent of the follicle unity. Melanocytes of the hair follicle have larger, more ramified melanosomes and the Golgi apparatus and rugged endoplasmic reticulum are better developed (26).…”
Section: The Melanocytesmentioning
confidence: 99%
“…Contradictory to a previous study (42), SNHG7 was preferentially located in the nucleus in both MEL270 and OMM2.5 cell lines in the present study. UM is significantly different from cutaneous melanoma and has unique tumorigenic processes and tumor biology (43). Thus, the present study suggests that the effect of SNHG7 in UM may be attributed to the specificity of the intraocular tumor.…”
Section: Discussionmentioning
confidence: 57%